The Burden of Cost in Bronchiolitis Obliterans Syndrome: Predictions for the Next Decade - Christopher A. Jones; David G. Chapman; Peter Weimersheimer; Luca Fernandez; Oscar Alejandro Mesa; Christian Peters; Bart M. Vanaudenaerde; Mitchell C. Norotsky; Robin Vos (Journal of Health Economics and Outcomes Research)
In health economics, costs can be divided into both direct and indirect categories. Direct costs tend to consist of medical costs, which are those directly attributed to health care interventions (e.g., hospitalizations, pharmaceuticals, devices), and non-medical direct costs such as monitoring and professional caregiving. Indirect costs tend to comprise those related to lost productivity due to illness (or treatment), burden on systems outside of the healthcare domain, and other costs that can sometimes outweigh the entire sum of direct healthcare costs.